2018
DOI: 10.1016/j.cogsc.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Resource efficiency impact on marble waste recycling towards sustainable green construction materials

Abstract: India is one of the biggest marble producing country in the world (~10%). State of Rajasthan has nearly 85% of marble production capacity. Recently, the massive quantity of marble waste fine particulates generated in marble industry has become a major environmental hazard issue. Major minerals present in marble waste are calcite (CaCO 3) and dolomite (CaMg (CO 3) 2). The particle sizes of marble waste particulates has been found to be 200 µm (D 90). The chemical composition of marble wastes reveals oxides of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…According to the estimations, the proportion of the MD being generated during the cutting of marble bricks is about 20-35%, however, this number highly depends on the size and the shape of the cut blocks [13]. Reportedly, there is about 12 million metric tons of this MD generated in India each year, with Rajasthan state being the number one in releasing the most [14]. Stone cutting is generally performed with the help of water, which plays a triple role by lubricating and cooling the cutting blades, while also collecting the dust with a typical particle size below 200 µm [15].…”
Section: Introductionmentioning
confidence: 99%
“…According to the estimations, the proportion of the MD being generated during the cutting of marble bricks is about 20-35%, however, this number highly depends on the size and the shape of the cut blocks [13]. Reportedly, there is about 12 million metric tons of this MD generated in India each year, with Rajasthan state being the number one in releasing the most [14]. Stone cutting is generally performed with the help of water, which plays a triple role by lubricating and cooling the cutting blades, while also collecting the dust with a typical particle size below 200 µm [15].…”
Section: Introductionmentioning
confidence: 99%
“…Tests were performed at different curing ages and the compression tests were done in Compression testing machine. There is a huge traffic for further research in recycling which makes sustainable and green materials, generating employment from marble waste concrete production ensures provision of income to urban and rural mass while arresting further pollution of the environment [6], [7]. Further research could be done on fire resistance, acid resistance, durability and flexural strength of this kind of ceramic waste tile concrete [8].…”
Section: Objectives Of the Studymentioning
confidence: 99%
“…The reaction process of geopolymers is a process of repolymerization after depolymerization. During this process, the fly ash spherical particles are dissolved, the Al-O and Si-O bonds are destroyed, and new non-crystalline gelatinous substances are formed [46][47][48][49][50][51][52][53][54]. The XRD patterns showed that the main components of the polymerization products were amorphous structures.…”
Section: Mineral Composition Characteristics Of Foamed Geopolymermentioning
confidence: 99%